A study on the early-stage decomposition in the Al-Mg-Si-Cu alloy AA6111 by electrical resistivity and three-dimensional atom probe - Esmaeili, S; Vaumousse, D; Zandbergen, M; Poole, W; Cerezo, A; Lloyd, D (2007)
Electrical resistivity measurements and three-dimensional atom probe (3DAP) analysis were employed to investigate early-stage decomposition of the Al alloy AA6111 in the temperature range 60-180C where electrical resistivity initially increased with ageing time. 3DAP measurements provided information on the shape, number density and solute content of the precipitates, as well as the solute concentration of the matrix, for the ageing conditions corresponding to the resistivity maxima. Using the 3DAP results, the precipitate size distributions for these ageing conditions were determined in terms of the measured number of solute atoms per precipitate. The number density and the Cu content of the precipitates decreased with increasing temperature, whereas the Mg/Si ratio increased. The size distribution of precipitates at the higher ageing temperatures showed the addition of larger size precipitates to the precipitate population. A modification to Matthiessen's law was employed to describe the anomalous resistivity increase by considering the effect of solutes and precipitates on the resistivity evolution. Using the 3DAP results in analysing the resistivity anomaly, it was found that the decrease in the resistivity maxima with increasing temperature was associated with the decrease in the number density of precipitates and not the scattering power of precipitates. The 3DAP results were further used to provide information on the mechanisms of early-stage decomposition and the temperature dependence of the nucleation rate. From this, the nucleation rate appeared to be controlled by the migration of solute atoms, which was assisted by quenched-in vacancies.